تجديد الدرس الحديثي في الجزائر عند الإمام أبي يعلى الزواوي - بوحمادو يونس (University of Elouedجامعة الوادي, 2024)
نّ درس الحديث النبوي قد مرّ بما مرّت به الفروع العلمية للدرس الإسلامي عموما؛ وذلك من جهتي الازدهار والركود، والجزائر لم تكن نشازا، فقد أدّت العوامل المادية والمعنوية للقطر الجزائري إلى ضعف الدّرس الحديثي؛ رواية ودراية، وهو ما دفع علماء الجزائر في القرن 14ه إلى الاعتناء به، والسعي إلى تجديد علومه ومعارفه، وتخليصه من ربقة الجمود والتقليد، وممن انخرط في هذا المسعى العلمي؛ الإمام أبو يعلى الزواوي، والذي شارك إخوانه من علماء الجزائر في هذا المشروع النهضوي الإسلامي، سالكا في ذلك مسالك علميّة ميّزته عن غيره، والتي سنشير إلى أبرزها في هذه الورقة البحثية المركّزة. The study of Prophetic Hadith has undergone fluctuations, akin to the general trends in Islamic education. Algeria, not exempt from these dynamics, witnessed a decline in the field of Hadith studies due to both material and moral factors. This prompted Algerian scholars in the 14th century to actively engage in revitalizing and renewing their knowledge, liberating it from the stagnation of tradition. Among those dedicated to this scholarly endeavor was Imam Abu Yaala Al-Zawawi, who collaborated with his fellow Algerian scholars in this Islamic renaissance project. He charted unique scientific paths that distinguished him from others, and this paper will highlight the prominent aspects of his contributions in this focused research
Keywords: التجديد; أبو يعلى الزواوي; الرّواية والدّراية; الحديث النبوي; Prophetic Hadith; Renewal; Abu Yaala Al-Zawawi; Narration and Knowledge